Lithuanian Statistics in the Context of Celebrating the World Statistics Day - Markelevičius, Jonas; Lapėnienė, Vilija (Lithuanian Journal of Statistics, 2010)
On the 3rd of July, the United Nations General Assembly, taking into consideration the decision of the Statistical Commission, has adopted a Resolution wherein it was decided to designate 20 October 2010 as the World Statistics Day. Aiming to focus on the core values of statistics, such as quality services, integrity and professionalism, the main topic of the celebration will be “Celebrating the many contributions and achievements of official statistics”. The official Lithuanian statistics meets the World Statistics Day not only by declaring but also by actually implementing the principles of statistics of a democratic state, complying with the standards of European statistics and satisfying the needs of national and foreign users of statistics. The article gives a brief overview of the pathways of national statistics stretching 90 years backwards, the development of statistical thought, statistical integration processes in democratic society, as well as discusses the significance of statistical capacity in preparing reliable and timely statistical information necessary to arrive at legitimate political decisions and to inform society, demonstrates the achievements of Lithuanian statistics over 20 years of independence, and mentions key statistical works to be implemented in the nearest future.